Penari menari ('dancing dancers') : Malay dance and Malay identity in Singapore, 1900s-present - Khairunnisa Nabilah Zainal Abidin (Nanyang Technological University, 2021)
This paper examines the historical evolution of Malay dance in Singapore since the 1900s and relates it to the formation of Malay identity. Drawing on personal interviews, newspaper articles as well as secondary sources such as books and journals, this paper studies the processes of change that Malay dance underwent. This paper has identified four key historical developments of Malay dance in Singapore: 1) classical Malay dance; Malay folk dance; 3) kreasi baru (‘new creations’) and; 4) contemporary Malay dance. Within and across these dance forms are various and competing ideas of ‘Malay’ and ‘Malayness.’ This thesis argues that Singapore Malay dance reflects and symbolises Malay identity in several ways, namely the centrality of the sultanate, the ‘familiarity’ of ‘Malayness,’ gender roles, and the blurring of the boundaries of ‘Malayness.’ This thesis also asserts that the historical evolution of Singapore Malay dance has affected its symbolism of Malay identity.